A digital platform to (re) link heritage of Malaysia : co-producing information concerning ICH / Irfan Ullah, Mokhtar Saidin and Abdul Mutalib - Irfan, Ullah; Mokhtar, Saidin; Abdul Mutalib, Abdul Razak (Universiti Teknologi MARA, Perak, 2018)
Since its implementation, the UNESCO’s Convention for the Protection and safeguarding of Tangible and Intangible Cultural Heritage (2003) remains a field of co-operation in what concerns its application in community and nation-wide strategies for the countries that approved the document. One of its the tangible influences has been the consciousness that new creativities must take place to recognise and document the living tradition of each region. Consequently, identifying Intangible Cultural Heritage is a keyword for the expansion of safeguarding and protection strategies, as it remains a dominant issue when it comes to pleasing to action any plan in this arena. The “Repository of Penang Cultural Diversity” is a working process project designed as a digital platform to enhance the broadcasting of knowledge and information about ICH in the Penang region (West Malaysia). It imagines a comprehensive approach to cultural heritage: material (buildings, objects, museum collections), intangible (know-how, cultural practices) and natural (cultural landscapes). Also, highlights a historical perception as well a modern view of how folk practices are taking place these days and highlights the active and developing nature of ICH. This short paper deliberates the concepts that guide the project, objectives and methodologies.